The Legitimacy of European Constitutional Orders A Comparative Inquiry - Dani, Marco; Goldoni, Marco; Menéndez, Agustín J. (Edward Elgar Publishing, 2023)
The Legitimacy of European Constitutional Orders is a systematic and comparative study of European constitutional orders, which takes into consideration the national constitutional trajectories of European countries, as well as the defining power of EU law. Drawing on a wealth of case studies, this book explores the conceptual tools needed to undertake comparative reconstruction and assessment of national and supranational constitutional developments in the European context.